Leaderpreneruship: Integration Between Enterpreneruship and Leadership in Strengthening the Tourism Economy in Ilomata Village, Bilato District, Gorontalo Regency - Danial, Haris; Bay, Indri Wirahmi; Dako, Rahman Taufiqriyanto; Pakaya, Usman (PT. Amirul Bangun Bangsa, 2024)
Ilomata Village is one of the villages in Bilato District, which is one of the centers of entrepreneurial activity in the region. Unfortunately, the lack of attention from the community and business actors, as well as leadership in upholding the tourism concept, is an obstacle to improving the tourism economy in the village. The ability to market tourism and businesses that are icons of the village is one of the biggest obstacles in the village. Moreover, the problem of English being a supporting system for improving the village economy requires intervention in regional development efforts. The MBKM